2010
DOI: 10.1016/j.visres.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intrinsically-photosensitive retinal ganglion cells on the spectral sensitivity and response dynamics of the human pupillary light reflex

Abstract: Historically, it was assumed that the light-evoked neural signals driving the human pupillary light reflex (PLR) originated exclusively from rod and cone photoreceptors. However, a novel melanopsin-containing photoreceptive cell class has recently been discovered in the mammalian retina. These intrinsically photosensitive retinal ganglion cells (ipRGCs) project to the pretectum, the retinorecipient area of the brain responsible for the PLR. This study was therefore designed to examine the relative contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
314
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(362 citation statements)
references
References 96 publications
26
314
1
8
Order By: Relevance
“…Alpern & Ohba 1972;Hansen & Fulton 1986;McDougal & Gamlin 2010). Further, McDougal and Gamlin have recently shown that mRGCs and rods contribute significantly to pupil constriction for test stimuli with duration of 100 s, whereas cones contribute little (McDougal & Gamlin 2010), suggesting that rod activity can influence the pupil even when using a steady background. We used bright stimuli with approximately 3640 scotopic trolands for the control stimulus and the lowest retinal illuminance used was approximately 1710 scotopic trolands throughout to eliminate the intrusion of rods.…”
Section: (G) Rod Intrusionmentioning
confidence: 99%
“…Alpern & Ohba 1972;Hansen & Fulton 1986;McDougal & Gamlin 2010). Further, McDougal and Gamlin have recently shown that mRGCs and rods contribute significantly to pupil constriction for test stimuli with duration of 100 s, whereas cones contribute little (McDougal & Gamlin 2010), suggesting that rod activity can influence the pupil even when using a steady background. We used bright stimuli with approximately 3640 scotopic trolands for the control stimulus and the lowest retinal illuminance used was approximately 1710 scotopic trolands throughout to eliminate the intrusion of rods.…”
Section: (G) Rod Intrusionmentioning
confidence: 99%
“…These cells express the photopigment melanopsin, with an action spectrum peaking at about 483 nm. These cells have been shown to exert significant control over the steady state pupil response in both macaque and human (Gamlin et al, 2007;McDougal & Gamlin, 2010). Thus while we have considered photopic luminance as the controlling variable, the action spectrum of the actual controlling quantity is likely to be a more complex mixture of rod, cone, and ipRGC sensitivities.…”
Section: Area Summation and Iprgcsmentioning
confidence: 99%
“…The newly defined PAP (phase amplitude percentage) metric , calculated as ( 638 −464 638 ) 100, used the phasic response during light stimulation to measure inner and outer retinal interactions. As ipRGCs contribute to maintaining pupil constriction during stimulus presentation, the peak-to-trough amplitude for the short wavelength sinusoid stimulus is lower than that of the long wavelength stimulus under normal conditions Güler et al 2008;McDougal & Gamlin 2010). In retinal disease conditions, ipRGC loss or dysfunction would reduce pupil constriction during light stimulation, resulting in a similar peak-to-trough amplitude for both high and low melanopsin excitation stimuli (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The inner retina includes the conventional ganglion cells (RGC) and melanopsin expressing ganglion cells (M 1 and M 2 in humans and primates) with dendrites that stratify in the inner plexiform layer (IPL) and which project to various centres in the brain that regulate image-forming functions (vision; green line) and non-imageforming functions (sleep, mood and pupil; brown lines). With projections to the olivary pretectal nucleus (OPN) that mediate the pupil light reflex (PLR) (Gamlin et al 2007;Lucas, Douglas & Foster 2001a;Markwell, Feigl & Zele 2010;McDougal & Gamlin 2010), ipRGC function can be measured in vivo.…”
Section: Statement Of Original Authorshipmentioning
confidence: 99%
See 1 more Smart Citation